PRINCIPLE OF LIMITED CAPACITY OF THE SUBASTHENOSPHERIC MANTLE - Abramovich I.I. (My University, 1990)
A wide range of tectonomagmatic phenomena in zones of plate interaction depends on the physical state of the mantle (or of its top 700-km layer), and especially on the rheology of its asthenospheric and subasthenospheric substrate. Theoretical modeling of heat and mass transfer on active place margins indicates that the concept of a spherically uniform structure of the upper mantle is inadequate and that models that take account of the lateral rheologic inhomogeneity of the mantle material are more instructive. Especially instructive is a model in which the rheologic properties of the subasthenospheric substrate at every instant are treated as the cumulative result of all preceding events. As an extension of this result, the author proposes the principle of limited capacity of subasthenospheric mantles, which defines the necessary conditions for congruent (in Dickinson's terminology) activity of the subduction zone. The principle is formulated as follows: As cold, viscous material from a subducting lithospheric plate accumulates in the subasthenospheric mantle, the potential for continuing subduction under any given conditions decreases, so that eventually subduction ceases at this site.